Akt–the Mammalian Target of Rapamycin (mTOR) Pathway Inhibition Increases Cervical Cancer Cell Chemosensitivity to Active Form of Irinotecan (SN-38) - Septiani, Leri; Hidayat, Yudi Mulyana; Effendi, Yusuf Sulaeman; Djuwantono, Tono; Luftimas, Dimas Erlangga; Faried, Ahmad (Faculty of Medicine Universitas Padjadjaran, 2013)
Objective: To investigate the molecular pathway of the cytotoxic effect of SN-38 in human cervical cancer cell lines.Methods: Two human cervical cancer cell lines were treated with various concentrations of irinotecan for 24–72 hours and the sensitivity was analysed using the MTT assay. Apoptosis was further observed through microscopic examinations. The protein expression was determined using Western blot analysis. Results: CaSki cells demonstrated the highest sensitivity to SN-38, whereas HeLa cells showed the lowest. In cervical cancer cells, SN-38 induced apoptosis through an intrinsic- and extrinsic-pathways. In addition, we showed that SN-38 downregulated the phosphorylation of Akt-mTOR pathways in CaSki cells, but not in HeLa cells. Interestingly, in HeLa cells, which were more suggestive of a resistant phenotype, pre-treatment with LY294002 and rapamycin inhibited activation of Akt-mTOR signaling and significantly enhanced the sensitivity of HeLa cells to SN-38. Conclusions: Irinotecan exerts its anti-neoplastic effects on cervical cancer cells by inducing apoptosis through caspase-cascade. Inhibition of Akt-mTOR, LY294002 and rapamycin, which is targeted to Akt-mTOR pathways, may sensitize irinotecan-resistant cervical cancer cells.Keywords: Akt-mTOR pathways anti-neoplastic drugs, cervix cancer cells, LY294002, rapamycin DOI: 10.15850/ijihs.v1n1.103